2014
DOI: 10.1021/ac501722r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Size, Anisotropy, and Density Heterogeneity of Nanoparticles by Sedimentation Velocity

Abstract: A critical problem in materials science is the accurate characterization of the size dependent properties of colloidal inorganic nanocrystals. Due to the intrinsic polydispersity present during synthesis, dispersions of such materials exhibit simultaneous heterogeneity in density ρ, molar mass M, and particle diameter d. The density increments ∂ρ/∂d and ∂ρ/∂M of these nanoparticles, if known, can then provide important information about crystal growth and particle size distributions. For most classes of nanocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 39 publications
1
71
0
2
Order By: Relevance
“…A possibility to determine the particle size and density in just one AUC experiment is the multidimensional approach of simultaneously fitting the sedimentation and diffusion coefficients. 51,52 For this, the frictional ratio which is the hydrodynamic diameter divided by the volume equivalent diameter has to be equal 1. For the CuInS 2 QDs investigated in this study this is a fair assumption since they are spherical in good approximation as shown by the TEM data of Fig.…”
Section: Investigation Of the Fractions Via Analytical Ultracentrifugmentioning
confidence: 99%
“…A possibility to determine the particle size and density in just one AUC experiment is the multidimensional approach of simultaneously fitting the sedimentation and diffusion coefficients. 51,52 For this, the frictional ratio which is the hydrodynamic diameter divided by the volume equivalent diameter has to be equal 1. For the CuInS 2 QDs investigated in this study this is a fair assumption since they are spherical in good approximation as shown by the TEM data of Fig.…”
Section: Investigation Of the Fractions Via Analytical Ultracentrifugmentioning
confidence: 99%
“…Applications in particle technology have gradually evolved within the last years. A very promising example is the investigation of heterogeneity in the shape, structure, and density of nanoparticles [11][12][13]. Outside the nanometer range, this method is certainly less important because the influence of diffusion is negligible and general approaches provide sufficient accuracy for technical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the resolution of AUC experiments has been significantly increased by applying more powerful techniques for data evaluation. [810] By means of this, size and shape distributions of various nanoparticles have been recently reported with high resolution. [1112] However, due to single-wavelength detection, correlations between size and optical properties could not be resolved.…”
mentioning
confidence: 99%